The study on the effectiveness on programs that implemented by Syarikat Bekalan Air Selangor (SYABAS) to maintain customer awareness / Norhafiza Shaari - Shaari, Norhafiza (Faculty of Business and Management, 2009)
Customer awareness is the major driving force for business sustainability and in today’s competitive global marketplace, it is recognized that high customer awareness is essential for the success of the firm. Nowadays to maintain and keeping the customers awareness is very difficult. Therefore, SYABAS do many programs as a line to maintaining customer awareness to their specialist service. Creating customer awareness is a core business challenge which has attracted considerable business attention. There many attributes that can develop customer awareness which are implemented by SYABAS such as customer open day, customer service centre (PUSPEL), campaign and public education program. Creating customer awareness is vital because when a customer know the existence of a service, customer will tend to purchase if it’s can satisfy the need of customer and also can reduce a customer complaint for the service. In this study, the findings show, there is strong relationship between public education and maintain customer’s awareness. In Malaysia, public education for people is very important nowadays to provide them all information. Public education is the best ways which SYABAS as a company that provides service for water supply must give the all information to make sure their customer aware about the important of water consumption.